Reurbanization and Spatially Polarized Land Markets – An Analysis of Urban Land-Value Changes in North Rhine-Westphalia, Germany, 2012–2024 - Siedentop, Stefan; Schartmann, Maximilian (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
In recent years, land prices in Germany have skyrocketed to levels that were hardly thought possible. This has particularly affected prospering cities, where price increases of more than 100 % have often been recorded since the turn of the millennium. The underlying causes are highly controversial. While some scholars point to the scarcity of developable land due to regulatory restrictions, others see the “financialization” of housing markets in the wake of the financial crisis and the massive influx of liquid capital into land and housing markets as the decisive driver. Against this background, this paper investigates the spatial patterns of land price dynamics in North Rhine-Westphalia during a phase of strong demographic and economic reurbanization. We used disaggregated data from the BORIS system for the years 2012 to 2024, which is available state-wide and georeferenced. Our empirical findings point to a significant trend of market polarization, with excessive growth rates in prospering metropolitan areas and real value losses in some rural areas. Overall, the paper offers new insights into the spatial patterns of urban land markets and possible driving factors explaining uneven developments.
Keywords: Land prices; Land market; Housing costs; Land use; Reurbanization; North Rhine-Westphalia; Germany